Modeling and Simulation of Silver-Based Filamentary Memristive Devices - Dirkmann, Sven; Trieschmann, Jan; Mussenbrock, Thomas (Bio-Inspired Information Pathways, 2024)
Memristive devices based on ﬁlamentary switching are investigated by 3D kinetic Monte Carlo simulations. The electrochemical metallization device under consideration consists of a stack of Ag/TiOx /Pt thin layers. By modeling the Ag ion transport within the solid state electrolyte, driven by the electric ﬁeld and thermal diffusion, the dynamics of resistive switching and conducting ﬁlament growth/dissolution are studied. The model allows to resolve the macroscopic time scale of consecutive growth and dissolution cycles. It provides realistic currentvoltage relations as observed experimentally. Simultaneously, it grants a detailed characterization of the inﬂuence of the electric ﬁeld and the thermal heat on the local resistive switching dynamics. It ﬁnally provides insight into the microscopic physical mechanisms involved in the set and reset kinetics during switching. It is concluded that the force due to electromigration on Ag in the closed ﬁlament may not be negligible during reset process of the device.